Analysis Of The Effect Of Curent Ratio, Debt To Equity Ratio And Net Profit Margin On Return On Equity (In Industrial Sector Companies) - Br Sitohang, Sri Devi Agustina; Aswin Akbar (Jurnal Ekonomi, 2024)
Any interested party may evaluate the company's financial performance with the help of the financial statements. Financial ratio analysis is a necessary tool for evaluating a business's performance. Financial performance measures include liquidity, solvency, profitability, and activity ratios, among others. The purpose of this study is to analyze industrial sector companies listed on the IDX to find out if the following ratios have any impact on return on equity: current ratio, debt to equity ratio, and net profit margin. Quantitative research methods are used. The data collection technique used in this study is non – participant observation. Companies in the industrial sector that are listed on the Indonesia Stock Exchange website (www.idx.co.id) were the subjects of the study. Secondary data was used in this investigation. For industrial sector businesses registered on the Indonesia Stock Exchange, the findings of the hypothesis t test indicate that ROE is unaffected by partly CR, DER, and NPM. In idx-listed industrial sector businesses, the findings of the hypothesis F test indicate that ROE is significantly affected by CR, DER, and NPM all at once.